Purchase Decision Model - Sudarso, Andriasan; Suryati, Lili (International Review of Management and Marketing, 2018)
The purpose of this research is to produce an empirical model of purchasing decision tickets for Railink transport Kualanamu Airport – Medan. This research was conducted by taking samples 200 of the 2,000 population respondents Passenger Train of the airport. The data for this study were collected using a questionnaire and analyzed by the method of survey explanatory. Methods of analysis used is line analysis. The findings of this study is an empirical model rise up purchase decisions train ticket Kualanamu Airport of Medan through promotion and pricing. Promotion in this case became the dominant factor to purchasing decision for train ticket to Kualanamu Airport Medan. Empirical model is formed due to the contribution of the promotion and price with 60.9%, so both those factors can determine purchase decisions more than the other factors which only 39.1%. Keywords: promotion, price, purchasing decisions JEL Classifications: M3, M51